Loyalty of Islamic banking costumers: A meta-analysis study - Widyarini, Widyarini (Journal of Islamic Economics Lariba, 2018)
This study was a meta-research, i.e., using some journals about topics that have the same flow, to be analyzed and drawn conclusions and suggestions. This research aims to provide an additional variable that idea 1) affect the decision to become a customer and 2) factors influence customer loyalty, particularly Islamic banks. The results show that the researchers were less sensitive against the selection of the respondent bank. Researchers should strictly separate between saving a customer with financing, voluntary or forced to have the saving. Each group has a different sensitivity. Variables that are influencing the decisions to a become a bank saving customers are Compliance, quality of service (Assurance, Responsiveness, Empathy, and Tangibles, Reliability). Future research needs the addition of Trust1 as variables to influence decision making becomes a customer. Trust2 and Religiosity (social piety) as variables change the satisfaction of the customer to become a loyalist.